Agriculture Value Chain — Challenges and Trends in Academia and Industry RUC-APS Volume 2 - Hernández, Jorge; Kacprzyk, Janusz (Studies in Systems, Decision and Control, 2025)
XXV, 294 p. 81 illus., 51 illus. in color.